2009
DOI: 10.1016/j.healun.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Angiotensin II Type 1 Receptor (AGTR1) is Associated With Age at Diagnosis in Pulmonary Arterial Hypertension

Abstract: Background Pulmonary arterial hypertension (PAH) is a rare, lethal disease associated with single gene disorders, connective tissue disease, exposures to anorexigens, and often idiopathic etiology. There is evidence that genes can modify the risk of PAH: 1) monogenic disorders associated with PAH are incompletely penetrant, and 2) not all patients with associated conditions at increased risk for PAH develop the disease. The renin angiotensin aldosterone system (RAAS) provides a set of candidate genes that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
22
2
Order By: Relevance
“…36 Other studies also did not show the positive association between rs1800875 and hypertension among Japanese, Russian, and American populations. [37][38][39] In the present study, no significant difference was found between the case group and the control group in the genotype as well as allele distributions of rs1800875 in the Chinese Han population. This finding was consistent with previous results among other populations.…”
Section: Discussioncontrasting
confidence: 73%
“…36 Other studies also did not show the positive association between rs1800875 and hypertension among Japanese, Russian, and American populations. [37][38][39] In the present study, no significant difference was found between the case group and the control group in the genotype as well as allele distributions of rs1800875 in the Chinese Han population. This finding was consistent with previous results among other populations.…”
Section: Discussioncontrasting
confidence: 73%
“…Endothelin 1 and angiotensin are major arterial constrictors and play significant roles in pulmonary hypertension. 2,75,76 Our data showed a significant downregulation of these molecules (Fig. 7D-7H), constituting a molecular protection profile for pulmonary arterial constriction.…”
Section: Resultsmentioning
confidence: 54%
“…The most likely candidate genes are Gga9:13.5-14.8: AGTR1, angiotensin II type 1 receptor; and UTS2D, urotensin receptor 2 D; Gga9:16-5HT2B, serotonin receptor/transporter type 2B; and Gga27:2-ACE, angiotensinogen cleaving enzyme. Each of these genes has been implicated in some aspect of hypertension or hypoxic response in mouse or humans (Simonneau et al, 2004;Watanabe et al, 2006;Djordjevic and Görlach, 2007;MacLean, 2007;Chung et al, 2009). Genes that we did not find include BMPR2, which has been implicated in human hypertension (De Caestecker Figure 4.…”
Section: Genetic Basis For the Ascites Syndromementioning
confidence: 85%